Agroturystyka jako rodzaj działalności rolniczej w prawie włoskim - Kapała, Anna (Wydawnictwo Naukowe UAM, 2007)
Polish legislation lacks one broad and comprehensive definition of agricultural activity. Legal regulations concerning farm tourism in Poland are dispersed in different legislation acts. Therefore it is worthwhile taking a closer view on the notion of farm tourism as an agricultural activity, or activity related to agriculture as defined in Italian law. The main deliberations are focused on the analysis of the criteria that connect farm tourism with agricultural activity as set out in Act 96/2006 on farm tourism. Those criteria are variable, detailed and they precisely determine the boundaries within which farm tourism may be conducted. In the concluding remarks, de lege ferenda on the notion of farm tourism in Polish law have been presented. The author points to the necessity (formulated already in the literature) of inserting into Polish legislation of the notion of agricultural activity. This should be performed in a systematic and coherent way, and the notion should include non only the traditional production activities but various related activities, such as farm tourism, as well. Doing it, however, shall require determination of clear criteria what related activities are, as only their fulfillment would allow to qualify farm tourism as an agricultural activity.